2023
DOI: 10.1002/adfm.202302112
|View full text |Cite
|
Sign up to set email alerts
|

Heptamethine Cyanine‐Based Nanotheranostics with Catalase‐Like Activity for Synergistic Phototherapy of Cancer

Abstract: Single‐molecule photosensitizers (PSs) for synergistic phototherapy are desirable but highly challenging, due to the competitive relationship between photothermal (PTT) and photodynamic therapy (PDT). Herein, a supramolecular strategy is developed that can tune the stacking pattern of PS molecules in their aggregates to optimize the PTT/PDT efficiency. Specifically, near‐infrared (NIR) heptamethine cyanines (Cy7) are synthesized using tricyanofuran (TCF) as the acceptor and benzothiazole (BTH)/indole (IND) as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Skin tissues surrounding the wounds were evaluated at the 10th day by histological examination [hematoxylin–eosin (H&E) and Masson dyes] to further characterize the wound healing efficacy. 30,38,39 As illustrated in Fig. 4e, H&E staining revealed that the control groups (treated with PBS or NPs only) had insufficient epidermis formation along with infiltrated inflammatory cells.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Skin tissues surrounding the wounds were evaluated at the 10th day by histological examination [hematoxylin–eosin (H&E) and Masson dyes] to further characterize the wound healing efficacy. 30,38,39 As illustrated in Fig. 4e, H&E staining revealed that the control groups (treated with PBS or NPs only) had insufficient epidermis formation along with infiltrated inflammatory cells.…”
Section: Resultsmentioning
confidence: 90%
“…Literature reports also showed that cyanine dyes could easily form large aggregates of various morphologies in aqueous solution, and the absorption spectra of these self-assembly systems caused by π–π stacking generally exhibited a blue-shifted absorption peak. 28,30,31 The blue shift phenomenon of the Flav7@DSPE-PEGG NPs was attributed to Flav 7 molecular aggregation due to π–π stacking. After excitation at 808 nm, fluorescence spectra of the Flav7@DSPE-PEGG NPs showed obvious fluorescence bands at 1000–1100 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 In addition, heptacyanine nanodiagnostics with catalase-like activity can be used for synergistic phototherapy of cancer. 27 From this perspective, the combination of photothermal and chemodynamic therapies is traceable.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Photothermal therapy (PTT), which involves the use of suitable photothermal agents to convert laser energy into heat, has been well developed due to its noninvasive, remotely controllable, tissue-penetrating specificities, and minimal side-effects. For example, heavy-atom-structured hypoxia-responsive probes for precise photoacoustic imaging and cancer therapy have been developed . In addition, heptacyanine nanodiagnostics with catalase-like activity can be used for synergistic phototherapy of cancer . From this perspective, the combination of photothermal and chemodynamic therapies is traceable.…”
Section: Introductionmentioning
confidence: 99%